A revised inventory of Adverse Childhood Experiences. (October 2015) - Finkelhor, David; Shattuck, Anne; Turner, Heather; Hamby, Sherry
Abstract: This study examines whether the items from the original Adverse Childhood Experiences (ACE) scale can be improved in their prediction of health outcomes by adding some additional widely recognized childhood adversities. The analyses come from the National Survey of Children's Exposure to Violence 2014, a telephone survey conducted from August 2013 through April 2014 with a nationally representative sample of 1, 949 children and adolescents aged 10–17 and their caregivers who were asked about adversities, physical health conditions and mental health symptoms. The addition of measures of peer victimization, peer isolation/rejection, and community violence exposure added significantly to the prediction of mental health symptoms, and the addition of a measure of low socioeconomic status (SES) added significantly to the prediction of physical health problems. A revised version of the ACES scale is proposed.